Pemaknaan Khalayak terhadap Resistensi Seksualitas Perempuan dalam Film Lipstic Under My Burkha - Ernest Wuri Indri Penny; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2019)
Active audience makes the text in a film become rich in meaning. That is because the audience actively produces meaning based on their background, experience, and daily life. Lipstick Under My Burkha is a film that seeks to offer alternatives to interpret female sexuality through the scenes in it. However, the meaning of active audiences is not necessarily in line with the idea of alternative meanings offered by the film. So this study aims to see the diversity of audiences against resistance by the four main female characters in the film. Using the type of qualitative research that refers to the critical paradigm with Stuart Hall's reception analysis method and Roland Barthes's semiotic data analysis. Theories used are Feminist Media and Film Theory, Hidden Transcript Theory and Reception Theory. This research has chosen nine preferred readings that display forms of women's resistance to the elements of sexuality contained in the film, namely elements of body image, intimacy, attraction and desire, fantacy, shared sexual behavior, and elements of partner or domestic violence. Resistance was raised by displaying female characters who liberated their sexuality to emerge from the myths of sexuality that had been exist. The results showed that almost all informants tended to be in a dominant position, but still negotiated the form of resistance in accordance with the values that the informant had previously believed. Informants tend to be in the dominant position of reading when confronted with the preferred reading of women's resistance through the elements of sexuality, body image, fantasy, shared sexual behavior, and partner or domestic violence. Where there are informants who have a similar situation with the main female character in the film and take the same resistance as the main characters in the film. Here, religious values are the most frequent reasons when informants will negotiate or reject the forms of resistance displayed by the Lipstick Under My Burkha film. Informants who are in negotiation or opposition positions tend to be active in diversity activities in their social environment, such as studies conducted at campus mosques. They also become followers of Islamic da'wah media accounts through their social media accounts. So, we can see that this alternative ideology for understanding women's sexuality is starting to have room to be accepted by Indonesian society.